The Plasma Membrane Ca2+-ATPase2 (PMCA2) Is Involved in the Regulation of Purkinje Cell Dendritic Growth in Cerebellar Organotypic Slice Cultures - Pradeep Sherkhane; Josef P. Kapfhammer (Neural Plasticity)
Purkinje cells are the principal neurons of the cerebellar cortex and have an extensive and elaborate dendritic tree. Chronic activation of type I metabotropic glutamate receptors inhibits Purkinje cell dendritic growth in organotypic cerebellar slice cultures. This effect is mediated by calcium influx through P/Q-type and T-type Ca2+ channels. We have now studied the role of the plasma membrane Ca2+-ATPase2 (PMCA2), a major calcium extrusion pump, for Purkinje cell dendritic development. We found that PMCA2 is strongly expressed in the plasma membrane and dendritic spines of Purkinje cells in organotypic slice cultures compatible with a role for controlling the local dendritic calcium equilibrium. Inhibition of PMCA2 activity by carboxyeosin resulted in a moderate reduction of Purkinje cell dendritic tree size indicating that the extrusion of calcium by PMCA2 is important for maintaining the dendritic calcium concentration and controlling dendritic growth. When inhibition of PMCA2 was combined with stimulation of type I metabotropic glutamate receptors, it partially rescued dendritic morphology. This protection can be explained by a compensatory inactivation of voltage-gated calcium channels in Purkinje cells after PMCA2 inhibition. Our results demonstrate that PMCA2 activity is an important regulator of the dendritic calcium equilibrium controlling Purkinje cell dendritic growth.